Sustained censorship in IR (2026-03) (Iran) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Iran. Data sourced from OONI.
Censorship Incident ID: IR-2026-0389. Severity: critical. Confidence: 80%